Morfologi Jenis Tembelekan (Lantana camara L.) di Beberapa Wilayah Kepulauan Buton (retracted due to double publication) - Jumiati, Jumiati; Andarias, s Hafidhawati (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2020)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other journal).